"I am not a babysitter": a case study of five Chinese mainland early childhood teachers' identity. Issue 1 (1st January 2017) - Zhang, Limin; Yu, Shulin
Abstract: Although studies on teacher identity have proliferated in recent years, and examinations of the said topic have been conducted under various educational contexts, limited focus has been given to teacher identity in the early childhood educational context. Drawing upon data from semi-structured interviews with five early childhood teachers, this case study aims to investigate how early childhood teachers make sense of their work and the type of professional identities constructed by early childhood teachers in mainland China. The five early childhood teachers reported strong disagreements with the babysitter metaphor for their teacher identities, and they had various role identities including 'parents', 'teachers', 'friends', 'dancers', 'artists', and 'engineers'. The findings also show that they recognized the significance and value of their job as early childhood teachers. This paper concludes with implications for early childhood teacher education.